Analisis Kadar Kalium (K) Pada Daun Sirih Merah (Piper crocatum Ruiz & Pav) Menggunakan Metode Spektrofotometri - Andi Kurnianingsih; Supriadi Supriadi (Media Eksakta, 2022)
Red betel is a vines that can grow in the tropics. This plant is known to the public as an ornamental plant and one of the traditional medicines to cure several types of diseases. This study aims to determine the level of potassium (K) contained in red betel leaf (Piper crocatum Ruiz & Pav). Potassium contents determined using an atomic absorption spectrophotometer (AAS). The results showed that the water content of red betel leaf was 84,6%, the ash content was 2,27% and the biomass content was 13,13%. While the average level of potassium in red betel leaf is 494,175 mg/100g.